SPIN-OFF DAN KONVERSI BANK UMUM KONVENSIONAL MENJADI BANK UMUM SYARIAH PADA BADAN USAHA MILIK DAERAH (BUMD) DI INDONESIA - Azani, Muhammad (ANDREW Law Center, 2025)
The spin-off and conversion of Conventional Commercial Banks (BUK) owned by Regional-Owned Enterprises (BUMD) into Sharia Commercial Banks (BUS) represent a strategic transformation facing challenges in harmonizing national policies with regional needs, as well as institutional governance complexities. This study aims to analyze the key factors determining the success or failure of the transformation process, and to evaluate the roles of institutional actors, governance structures, business strategies, and alignment of national policies within the regional context. The research employs a normative juridical method with a qualitative approach, through the analysis of regulatory documents, policies, and relevant literature. The findings indicate that the success of spin-off and conversion heavily depends on the synergy between regional governments, BUMD management, transparent governance, and adaptive, contextual business strategies. However, challenges such as regulatory disharmony and limited resources remain significant obstacles. These results contribute to the development of institutional theory and practical transformation of Islamic banking, emphasizing the need for more flexible regulations and policies that are responsive to regional conditions to support sustainable transformation. The social implications include enhancing financial inclusion and promoting more equitable regional economic development with syariah contract